Unveiling The Effect of Entrepreneurship Education, Curriculum and Lecturer Competency Toward Grit Entrepreneurial (Evidence: Higher Education Student in Bandung) - Saputra, Yori Andes; Wahyudin, Dinn (Westscience Press, 2024)
This study aims to unveil the effect of entrepreneurship education, curriculum, and lecturer competency on entrepreneurial grit among higher education students in Bandung. The research employs a quantitative approach, utilizing questionnaires as the primary data collection instrument. A total of 83 respondents, all higher education students in Bandung, participated in the survey. The data were subjected to statistical analysis to determine the impact of the three variables on entrepreneurial grit, defined as the perseverance and passion for long-term goals in entrepreneurship. The results of the analysis indicate that the curriculum does not have a significant influence on entrepreneurial grit. This suggests that the structure and content of the curriculum alone may not be sufficient to cultivate the necessary traits for entrepreneurial success. On the other hand, entrepreneurship education and lecturer competency were found to have a positive and significant impact on entrepreneurial grit. This underscores the importance of well-designed entrepreneurship education programs and the crucial role of competent lecturers in fostering and nurturing entrepreneurial qualities in students. These findings provide valuable insights for educational institutions aiming to enhance their entrepreneurship programs. By focusing on the quality of entrepreneurship education and the competencies of their lecturers, institutions can better support the development of entrepreneurial grit among their students. This study highlights the need for a more holistic approach to entrepreneurship education, where both the content and delivery by skilled educators are given priority to effectively cultivate future entrepreneurs.